2003
DOI: 10.1897/1551-5028(2003)22<1448:ivaiva>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Assessment of the Androgenic Potential of a Pulp and Paper Mill Effluent

Abstract: The androgenic potential of a New Zealand pulp and paper mill effluent was measured by applying a combination of in vitro and in vivo bioassays with mosquitofish (Gambusia affinis) and goldfish (Carassius auratus). The in vivo method assessed the rate of gonopodial development (masculinization) and alterations from normal reproductive behavior in adult female mosquitofish exposed for 21 d to untreated or secondary-treated pulp mill effluent. A second in vivo mosquitofish exposure tested the effect of glass-fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 22 publications
(41 reference statements)
2
44
1
2
Order By: Relevance
“…In the fi rst mosquitofi sh experiment, signifi cant masculinization was demonstrated at all effl uent concentrations of treated and untreated effl uent (Ellis et al 2003). Treatment appeared to remove some of the androgenic potency of the effl uent, though masculinization was still present at environmentally relevant concentrations of 15% effl uent.…”
Section: Laboratory Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…In the fi rst mosquitofi sh experiment, signifi cant masculinization was demonstrated at all effl uent concentrations of treated and untreated effl uent (Ellis et al 2003). Treatment appeared to remove some of the androgenic potency of the effl uent, though masculinization was still present at environmentally relevant concentrations of 15% effl uent.…”
Section: Laboratory Studiesmentioning
confidence: 98%
“…This bioassay takes advantage of the sexual dimorphism in male and female mosquitofi sh with the male possessing an elongated anal fi n which acts as a sexual organ. This organ, called a gonopodium, can be grown in a female exposed to endogenous androgenic compounds (Ellis et al 2003).…”
Section: Laboratory Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fish exposed to pulp mill effl uents in both fi eld and laboratory studies have shown alterations in their reproductive performance, including reduced gonad size (Munkittrick et al 1992;Parrott et al 2004), reduced egg production (Parrott et al 2004;Rickwood et al 2006), delays in maturation (Munkittrick et al 1992), male-biased sex ratios (Larsson et al 2000;Örn et al 2006), masculinization of females (Larsson and Förlin 2002;Ellis et al 2003), reduced development of secondary sexual characteristics (McMaster et al 1991), and depressed steroid hormone levels (Munkittrick et al 1992;Dubé and MacLatchy 2000).…”
Section: Introductionmentioning
confidence: 99%